Critical angle of attack and the corresponding impact cavity for non-circuitous trajectory of water entry of circular cylinder. (October 2020) - Xia, Weixue; Cong, Wang; Wei, Yingjie; Li, Conghui
Abstract: The critical initial angle of attack that the cylinder can move along the non-circuitous trajectory in water entry is investigated experimentally and numerically. A primary focus is on characterizing the relationship between the initial inclined angle α 0 and horizontal velocity u 0 in the parameters space of α 0 ∼ u 0 / v 0, where u 0 / v 0 is the horizontal velocity u 0 to vertical velocity v 0 ratio. To build a dense initial parameter space to capture the accurate critical curvature boundary (CCB), which is the critical parameters of the cylinder moving along a non-circuitous trajectory, a substantial water entry experiment is performed for the cylinder with different initial inclined angles and horizontal velocities. In this experiment, a high-speed camera is employed to record the position and the inclined angle of the cylinder. In addition, a large eddy simulation method is used to simulate some particular water entry cases that the cylinder initial parameters are near the CCB space. After the analysis, the initial parameter space for the oblique water entry almost locates in the left circuitous space. Based on the equation of the oblique water entry in the parameter space of α 0 ∼ u 0 / v 0, an empirical equation of CCB is established by giving a correction item of deviation angle of attack. When the initial parameters of the cylinder satisfy the equation of CCB, the cylinder first moves along the initial line Lu and then along the offset line Ld . The offset distance d offset between these two lines first increases with α 0 and u 0 / v 0 and then gradually tends to a constant about d offset / D  = 1, where D is the diameter of the cylinder. Moreover, the simulation results indicate that the pressure distribution on the cylinder surface is affected by the impact velocity, the wettability of the cylinder surface, the initial angle of attack and the distance between the cylinder surface and the pinch-off location.